2017
DOI: 10.3389/fmicb.2017.01714
|View full text |Cite
|
Sign up to set email alerts
|

PnpM, a LysR-Type Transcriptional Regulator Activates the Hydroquinone Pathway in para-Nitrophenol Degradation in Pseudomonas sp. Strain WBC-3

Abstract: A LysR-type transcriptional regulator (LTTR), PnpR, has previously been shown to activate the transcription of operons pnpA, pnpB, and pnpCDEFG for para-nitrophenol (PNP) degradation in Pseudomonas sp. strain WBC-3. Further preliminary evidence suggested the possible presence of an LTTR additional binding site in the promoter region of pnpCDEFG. In this study, an additional LTTR PnpM, which shows 44% homology to PnpR, was determined to activate the expression of pnpCDEFG. Interestingly, a pnpM-deleted WBC-3 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…His-tagged proteins were purified via Ni 2ϩ -nitrilotriacetic acid agarose chromatography (Novagen), eluted using 100 mM imidazole, dialyzed against phosphate-buffered saline (PBS) (50 mM, pH 7.0) at 4°C for 24 h, and analyzed via 12.5% SDS-PAGE. The oligomeric state of the native protein was determined via gel filtration chromatography (37). HpaM was loaded onto a column of Superdex 2000 (GE Healthcare AKTA Prime liquid system) that was equilibrated with 10 mM Tris-HCl buffer (pH 7.5, with 0.1 M NaCl and 5% glycerol) at a flow rate of 1 ml min Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
“…His-tagged proteins were purified via Ni 2ϩ -nitrilotriacetic acid agarose chromatography (Novagen), eluted using 100 mM imidazole, dialyzed against phosphate-buffered saline (PBS) (50 mM, pH 7.0) at 4°C for 24 h, and analyzed via 12.5% SDS-PAGE. The oligomeric state of the native protein was determined via gel filtration chromatography (37). HpaM was loaded onto a column of Superdex 2000 (GE Healthcare AKTA Prime liquid system) that was equilibrated with 10 mM Tris-HCl buffer (pH 7.5, with 0.1 M NaCl and 5% glycerol) at a flow rate of 1 ml min Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
“…The plasmid was then transformed into mobilizer strain E. coli WM3064 ( Table 1). The suicide plasmid in WM3064 was transformed to strain CNP-8 by biparental mating [32,33]. The double-crossover recombinant of was screened on LB plates containing sucrose (10%, w/v) and chloramphenicol (34 μg/ ml), and the mutant strain CNP-8ΔhnpA was confirmed by PCR analysis.…”
Section: Gene Knockout and Complementationmentioning
confidence: 99%
“…Chen et al (2016) mention multiple components, including transcriptional regulators and other unknown factors that regulate PNP degradation in Pseudomonas putida DLL-E4, as the transcriptional regulator type LysR (LTTR) activates the expression of genes in response to the specific inducer PNP. Also, Wang et al (2017) mention that a LTTR, PnpR, has previously been shown to activate the transcription of operons pnpABCDEFG for PNP degradation in Pseudomonas sp. strain WBC-3.…”
Section: Discussionmentioning
confidence: 99%